EMT exam prep : focused prep for the NREMT cognitive exam - Discua, Jessica (Kaplan North America, LLC dba Kaplan Publishing, 2025)
"Kaplan's EMT Exam Prep provides efficient review and expert test-taking strategies for passing the EMT certification exam of the National Registry of Emergency Medical Technicians (NREMT)"--